2018
DOI: 10.1002/mnfr.201800707
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrosides from Sea Cucumber Improved Aβ1–42‐Induced Cognitive Deficiency in a Rat Model of Alzheimer's Disease

Abstract: Scope Cerebrosides are a class of neutral glycosphingolipids, which are widely found to be present in brain tissue. In this study, the protective effect of sea cucumber cerebrosides (Cer) against β‐amyloid (Aβ)‐induced cognitive impairment is investigated. Methods and results Male SD rats receive a ventricle injection Aβ1–42 peptide to establish an Alzheimer's disease model. Then, the protective effects of Cer against Aβ1–42‐induced cognitive impairment by gavage and feed addition are evaluated. The Morris wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 48 publications
(65 reference statements)
1
30
0
Order By: Relevance
“…Due to this unique structure, cerebrosides have various biological activities and, as a result, have attracted pharmaceutical research attention. In Li et al’s study [ 44 ], an AD rat model was obtained by intraventricular injection of Aβ1–42 and treated with cerebrosides by intragastric administration. Initially, the Morris water maze results indicated that oral administration of sea cucumber cerebrosides could significantly ameliorate the impaired cognitive function in Aβ1–42-treated rats.…”
Section: Marine Drugs In Alzheimer’s Diseasementioning
confidence: 99%
“…Due to this unique structure, cerebrosides have various biological activities and, as a result, have attracted pharmaceutical research attention. In Li et al’s study [ 44 ], an AD rat model was obtained by intraventricular injection of Aβ1–42 and treated with cerebrosides by intragastric administration. Initially, the Morris water maze results indicated that oral administration of sea cucumber cerebrosides could significantly ameliorate the impaired cognitive function in Aβ1–42-treated rats.…”
Section: Marine Drugs In Alzheimer’s Diseasementioning
confidence: 99%
“…A β accumulation was proved to be able to lead to neuronal apoptosis, which was regulated by some regulators, such as the antiapoptotic Bcl-2 and proapoptotic Bax. It has been reported that the relative expression of Bax/Bcl-2 was significantly increased in A β 1-42 -injected rats compared with that of the sham group rats, and neuronal apoptosis will be caused by intracerebroventricular injection of A β 1-42 [ 31 , 32 ]. Apoptosis is the main reason for the loss of dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…One study investigated the protective effects of sea cucumber-derived cerebrosides against amyloid-β-induced cognitive impairment on AD male rat models. Results proved the neuroprotective capacity of the marine-derived glycolipids by ameliorating neuronal damage and suppressing the induced apoptosis [180]. Moreover, gangliosides, a family of glycosphingolipids containing sialic acid linked to an oligoglycosyl backbone, which is further attached to a ceramide base, are highly expressed in vertebrate nervous systems [181].…”
Section: Marine Lipids and Glycolipids For Neuroprotectionmentioning
confidence: 92%